Disegno, Memoria, Progetto (diségno, 2017)
As part of the events for the 210th anniversary of the foundation of the University of Palermo, on December 2, 2016, the exhibition Disegno, Memoria, Progetto was inaugurated, in which the graphic and multimedia elaborations of the courses and researches of the Drawing area of the Department of Architecture of Palermo were shown. The event, curated by Vincenza Garofalo and Francesco Maggio with the scientific responsibility of Nunzio Marsiglia, has been el- egantly set up at the exhibition hall of the former Faculty of Architecture in Viale delle Scienze. The inauguration of the exhibition was an occa- sion for a common reflection, which, after institutional greetings, provided for an introductory speech by Nunzio Marsiglia, followed by the views of the president of UID Vito Cardone, Francesca Fatta and me.